The bike deconstructed a grand tour of the road bicycle - Hallett, Richard 1960- (Mitchell Beazley, 2014)
Do you know the difference between a head tube and a headset? Can you tell whether a frame is made from steel or carbon fibre? Do you know how a derailleur works and why it revolutionized bike design? If not, this is the perfect guide for you. The Bike Deconstructed celebrates bicycle design by looking at its individual components, large and small. Their historical roots are explored, key features identified and principal uses (and sometimes misuses) revealed. Along the way, you'll lean how they are made, how they function, and why we need so many different variations.